Benchmarking the pediatric quality of life (PedsQL) cancer module in a large Dutch national cohort of childhood cancer patients - Elin Irestorm; Anne Bakker; Wim J. E. Tissing; Heleen Maurice-Stam; Natasja Dors; Annelies Mavinkurve-Groothuis; Sabine L. A. Plasschaert; Kelly L. A. van Bindsbergen; Martha A. Grootenhuis; Raphaele R. L. van Litsenburg (BMC Cancer)
Abstract Background Pediatric cancer diagnosis and treatment reduce Health-Related Quality of Life (HRQoL). The Pediatric Quality of Life (PedsQL) Cancer Module is the most commonly used cancer specific HRQoL instrument, but most studies included relatively small cohorts and no reference scores are available. The development of a PedsQL Cancer Module benchmark, based on a large population of pediatric cancer patients, may benefit future research by providing insight into issues children encounter during treatment or clinical trials. A benchmark would also allow for earlier identification of patients who may benefit from targeted interventions in HRQoL monitoring programs. The primary aim of this study was therefore to provide benchmark scores from a large national cohort for use in pediatric oncology care and research. Secondary aims were to compare scores between subgroups (age, sex, and diagnosis group) and to describe the prevalence of impaired HRQoL. Methods Data was collected from a national HRQoL monitoring program and extracted from medical records. HRQoL was measured with the PedsQL Cancer Module during treatment for childhood cancer, approximately 3 months after diagnosis. Comparisons were made for sex, age and diagnosis groups: hemato-oncology (HO), central nervous system-tumors (CNS), and solid tumors (ST) using the Mann-Whitney U test for the different subscales. Effect sizes were calculated. Impairment was defined on item level using descriptive statistics. Results Proxy-reports of 492 children (age 2–7 years) and self-reports of 500 children (age 8–18 years) were available. HRQoL differences between age groups, sex and diagnosis groups were small, with the exception of nausea. On the nausea subscale there was a medium effect size difference with children with ST reporting more problems than children with CNS. Impaired HRQoL was most often reported on items reflecting nausea and procedural anxiety. Conclusions Early in the cancer trajectory, there are only minor differences between subgroups based on age, sex, and diagnosis group. These results from a large national cohort can be used as benchmark data in future clinical trials, studies and clinical assessments, and offer and adapt support targeted for improving HRQoL related to treatment for childhood cancer.